Big History versus Cosmic History: A Review of Ted Peters’ Book - Gustafson, Lowell (Theology and science, 2021)
In God in Cosmic History, Ted Peters seeks to establish cosmic history by incorporating religion and the God question into big history. Peters begins with an evidence-based narrative just as big historians do, but his theological assertions regarding God as the author of cosmic history take us beyond where scientific knowledge will allow us to go. We still need to find new ways to express ancient wisdom that are not inconsistent with science. Ted Peters sets us off on a very useful path to do this, but the journey is still underway.